Philosophical and theological essays on the Trinity - Rea, Michael C.; McCall, Thomas H. (Oxford University Press, 2009)
How can we coherently believe that there is only one God if we also believe that there are three divine Persons? This volume presents a selection of the most important recent philosophical work on this topic accompanied by new essays from differing theological and philosophical perspectives.